A Novel Microstrip-to-Microstrip Vertical Via Transition in X-Band Multilayer Packages - M. X. Yu (International Journal of Antennas and Propagation)
This paper investigates a novel X-band microstrip-to-microstrip vertical via transition with matching pads loaded signal via. This design has been proposed for a multilayer substrate package. The matching pads, which are located in the center of the signal via on each ground layer, are adopted to further improve the impedance matching level and thus attain better signal transition performance. A physics-based equivalent circuit modeling approach has been employed for this research. The right angle MS-to-MS via transition was also designed using this technique. The simulated S-parameters indicate that the match-pad design made a breakthrough in achieving an approximate −15 dB wide-band return loss reduction. The measured S-parameter of MS-to-MS transition showed that return loss with the matching pads is better than that without the matching pads.